Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Indomarco Prismatama Cabang Bogor 2 - Fitriah Yusuf; Metehsa Sembiring; Jeffry H. Sinaulan (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Human resource management has become a determining role in operational systems in this modern era. The stronger the role of HRM, innovations in HRM managerial models always occur. This research aims to determine the influence of the work environment and work motivation on employee performance. This research uses an associative approach method to analyze the relationship between two or more variables, namely the influence of the work environment and work motivation on employee performance. The sample for this research is employees at PT. Indomarco Prismatama Bogor 2 branch has 54 employees. Data collection used questionnaires and interviews then continued with validity testing ending with hypothesis testing through regression coefficient analysis. Based on the research results, it was found that the work environment has a significant effect on the performance of PT employees. Indomarco Prismatama Bogor 2 Branch was 63.9% while the remaining 36.1% was due to other factors not included in this study (hypothesis 1 was proven). Work motivation has a significant effect on the performance of PT employees. Indomarco Prismatama Bogor Branch 2 amounted to 73.1%, while the remaining 26.9% was influenced by other variables not studied (hypothesis 2 was proven). From the test results of the influence of X1 and Indomarco Prismatama Bogor Branch 2 was 71.4% while the remaining 28.6% was due to other variables not studied (hypothesis 3 was proven).